The Relationships between Organizational Culture,Organizational Capital and Organizational Innovation among Faculty Members at Northern Border University - bin Fahs Radhi Al-Anzi, Atallah (Journal of College of Education, 2022)
AbstractThe study aimed to reveal the correlational relationships between organizational culture, organizational capital, and organizational creativity among faculty members at Northern Border University, and to reveal the predictive ability of organizational innovation from organizational culture, and organizational capital, and to reveal the mediating role of organizational capital in the relationship between organizational culture and organizational innovation. The sample of the study consisted of (110) faculty members. The study instruments consisted of three scales; The organizational culture scale, the organizational capital scale, and the organizational innovation scale. The results of the study indicated a positive and strong correlation between organizational culture and organizational innovation,  a positive and strong correlation between organizational culture and organizational capital, and  a positive and strong correlation between organizational capital and organizational innovation, and also indicated the predictive ability of both organizational culture and organizational capital by  Organizational innovation , and the predictive ability of organizational culture with organizational capital. The results indicated that organizational capital mediates the relationship between organizational culture and organizational innovation.
Keywords: Organizational culture; Organizational capital; Organizational innovation; Staff members; Northern Border University